Comment: The Economics of Nonmonetary Variables - Goode, William J. (Journal of Political Economy, 1974)
In the history of science researchers have often borrowed theories, analogies, or metaphors from other fields, usually the better-developed ones; in economic terms, they invested their human capital by acquiring new and presumably more-advanced intellectual tools.The most conspicuous borrowing in nineteenth-century social science was the unfortunately imaginary set of the developmental sequences of societies, worked out by anthropology and sociology on the basis of findings from biological evolution.It is less often that scientists in a relatively developed